MicroRNAs in the Pathogenesis of Hepatocellular Carcinoma: A Review - Morishita, Asahiro; Oura, Kyoko; Tadokoro, Tomoko; Fujita, Koji; Tani, Joji; Masaki, Tsutomu (Cancers, 2021)
Hepatocellular carcinoma (HCC) is the seventh most frequent cancer and the fourth leading cause of cancer mortality worldwide. Despite substantial advances in therapeutic strategies, the prognosis of late-stage HCC remains dismal because of the high recurrence rate. A better understanding of the etiology of HCC is therefore necessary to improve outcomes. MicroRNAs (miRNAs) are small, endogenous, noncoding, single-stranded RNAs that modulate the expression of their target genes at the posttranscriptional and translational levels. Aberrant expression of miRNAs has frequently been detected in cancer-associated genomic regions or fragile sites in various human cancers and has been observed in both HCC cells and tissues. The precise patterns of aberrant miRNA expression differ depending on disease etiology, including various causes of hepatocarcinogenesis, such as viral hepatitis, alcoholic liver disease, or nonalcoholic steatohepatitis. However, little is known about the underlying mechanisms and the association of miRNAs with the pathogenesis of HCC of various etiologies. In the present review, we summarize the key mechanisms of miRNAs in the pathogenesis of HCC and emphasize their potential utility as valuable diagnostic and prognostic biomarkers, as well as innovative therapeutic targets, in HCC diagnosis and treatment.